Decolorization of textile dyes in an air-lift bioreactor inoculated with Bjerkandera adusta OBR105. Issue 11 (19th September 2017) - Sodaneath, Hong; Lee, Jung-In; Yang, Seung-Ok; Jung, Hyekyeng; Ryu, Hee Wook; Cho, Kyung-Suk
ABSTRACT: A new decolorizing white-rot fungus, OBR105, was isolated from Mount Odae in South Korea and identified by the morphological characterization of its fruit body and spores and partial 18s rDNA sequences. The ligninolytic enzyme activity of OBR105 was studied to characterize their decolorizing mechanism using a spectrophotometric enzyme assay. For the evaluation of the decolorization capacity of OBR105, the isolate was incubated in an erlenmeyer flask and in an airlifte bioreator with potato dextrose broth (PDB) medium supplemented with each dye. In addition, the decolorization efficiency of real textile wastewater was evaluated in an airlift bioreactor inoculated with the isolate. The isolate was identified as Bjerkandera adusta and had ligninolytic enzymes such as laccase, lignin peroxidase (LiP), and Mn-dependent peroxidase (MnP). Its LiP activity was higher than its MnP and laccase activities. B. adusta OBR105 successfully decolorized reactive dyes (red 120, blue 4, orange 16, and black 5) and acid dyes (red 114, blue 62, orange 7, and black 172). B. adusta OBR105 decolorized 91–99% of 200 mg L −1 of each dye (except acid orange 7) within 3 days in a PDB medium at 28°C, pH 5, and 150 rpm. This fungus decolorized only 45% of 200 mg L −1 acid orange 7 (single azo-type dye) within 3 days, and the decolorization efficiency did not increase by prolonging the cultivation time. In the air-lift bioreactor, B. adusta OBR105 displayed a high decolorization capacity, greater than 90%, for 3 acid dyes (red 114, blue 62, and black 172) and 1 reactive dye (blue 4) within 10–15 h of treatment. B. adusta OBR105 could decolorize real textile wastewater in the air-lift bioreactor. This result suggests that an air-lift reactor employing B. adusta OBR105 is a promising bioreactor for the treatment of dye wastewater.